Remotion of physicochemical and microbiological parameters on wastewater treatment plants in Costa Rica’s Great Metropolitan Area - Chacón-Jiménez, Luz María (2023)
Inefficient treated wastewaters are a critical factor for public health due to can be a dissemination vehicle for pathogens such as enteric viruses; nevertheless, the enteric viral circulation has been poorly studied in our region. This work aims to study the presence of five enteric virus, in parallel with operative parameters, in affluents and effluents of five wastewater treatment plants (WWTP) located in the Greater Metropolitan Area of Costa Rica in 2013. The viral pathogens studied were enterovirus, hepatitis A virus, rotavirus A, and norovirus GI and GII (determined by end point PCR technique); since basic control parameters analyzed were biochemical oxygen demand, chemical oxygen demand, suspended solids, settable solids, fats and oils, blue methylene active substances, and fecal coliforms. All wastewater treatment plants showed acceptable removal of physicochemical parameters, but with microbial parameters, its efficiency was low; all enteric viruses were detected year-round at effluents and influents of the WWTP, with a predominance during the dry season. The most frequently detected virus was rotavirus, followed by norovirus G1. In conclusion, the studied wastewater treatment plants are efficient to remove physicochemical parameters; the year circulation of enteric virus in Costa Rica was demonstrated, and finally, a wastewater treatment plant improvement it is necessary to achieved treated waters safety discharges.